The Culture of Life Organization as an Institutional Project of Intergenerational Relations - Simonyan, Hamlet (Bulletin of Yerevan University E: Philosophy, Psychology, 2024)
In the contemporary world, humanity faces numerous socio-cultural and civilizational transformations that fundamentally alter the traditional image of the world, introducing new principles and mechanisms for organizing and regulating everyday life, as well as different value and worldview priorities, and preferences. Consequently, a new socio-cultural context emerges, where it becomes impossible to adhere to the principles and rules of the culture of life organization established by our ancestors. The problem is that the culture of coexistence in formerly traditionalist societies remained largely untouched by radical transformations, with each successive generation willingly conforming to the demands and compulsions of that cultural institution governing everyday life. However, the situation in our fast-paced world has undergone significant changes. The socio-cultural context of post-modernity undergoes constant editing and re-editing. Even within the span of a single generation, such radical changes occur that life circumstances present numerous challenges and dead ends. The methods and approaches to resolving these challenges were simply not anticipated in the culture of life organization of previous generations. Given this reality, the article presents the culture of organizing and regulating life as an institutional system that defines and regulates intergenerational relationships. It is viewed as an empirical ideology, the modernization of which holds significant scientific and practical importance.